The Influence of student self-efficacy and lecturer leadership on student ocb - Aini, Rohana Nur; Irianto, Ellen D Oktanti; Widaryo, Chandika Mahendra (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
This study aims to analyze the influence of student self-efficacy and lecturer leadership on the organizational citizenship behavior (OCB) of students in higher education. Using the library research method with a qualitative approach, this study explores the complex interactions between internal and external factors that shape students' organizational citizenship behavior. The results of the study revealed that student self-efficacy, which is manifested in academic beliefs, social efficacy, emotional regulation, and resilience to adversity has a significant effect on the dimension of student OCB through organizational identification mechanisms and intrinsic motivation. Lecture leadership, especially transformational leadership styles, creates a learning climate that encourages the internalization of prosocial values. The innovative finding of this study is the identification of compensatory interaction patterns, where the influence of lecturer leadership on student OCB is stronger in students with low to moderate self-efficacy. The implication is that universities need to develop an integrative approach that simultaneously strengthens student self-efficacy and lecturer leadership capacity to cultivate student OCB in a sustainable manner